Fabrication of AA1060/Al2O3 Composites by Warm Accumulative Roll Bonding Process and Investigation of its Mechanical Properties and Microstructural Evolution - M. Heydari Vini; P. Farhadipour (International Journal of Advanced Design and Manufacturing Technology, 2017)
Recently accumulative roll bonding (ARB) has been used as a novel method to produce particle reinforced metal matrix composites. The accumulative roll bonding as a severe plastic deformation (SPD) rolling procedure aimed at enhancing the mechanical properties of metals and alloys. The process consists in rolling series of overlapped sheets with a thickness reduction ratio (e.g. 50%). In this study, warm accumulative roll bonding (Warm- ARB) process has been used to produce Aluminum Metal Matrix Composite (AMMC: AA1060/-5% Al2O3). AA1060 strips were roll bonded as alternate layers up to 5 rolling passes with 300°C preheating for 5 minutes before each pass. The microstructure and mechanical properties of composites have been studied after different Warm- ARB passes by tensile test, Vickers micro hardness test and scanning electron microscopy (SEM). The results demonstrated that adding alumina particles into AMMCs improves both the strength and tensile toughness of composites. Moreover, the fracture surfaces of samples after the tensile test have been studied during various ARB cycles by scanning electron microscopy (SEM). Also, the results showed that mechanical properties such as tensile strength and average Vickers micro hardness improved with increasing the number of warm ARB cycles. Also, the elongation and tensile toughness of samples dropped in the primary cycles and improved in continuing with increasing the warm ARB cycles. Finally, warm ARB process would allow producing particle reinforced with good mechanical properties.